How Information Literacy Influences Student’s Online Risk Mitigation - Ghea Sekar Palupi; Paramitha Nerisafitra; Rahadian Bisma (JIEET (Journal of Information Engineering and Educational Technology), 2022)
The emergence of the COVID-19 pandemic has changed the learning system in higher education which is becoming distance learning using information technology. In addition to providing good opportunities, online learning poses risks that can threaten students. The risks encountered can be sourced from the information aspect. This study aims to determine the level of the role of information literacy which includes skills to obtain, analyze, and evaluate information, on students' awareness of online risk exposure. In this study, a survey was conducted to 264 undergraduate students at various universities in Indonesia. Data analysis was carried out using the SEM-PLS method with the help of SmartPLS 3.0 software to measure the construct of the hypothetical model. The results show that information literacy has a positive relationship with students' awareness of online risks. The relationship is mediated by the existence of self-control and awareness of information privacy by the individual. Therefore, the relationship means that the higher the level of information literacy, the students will be more aware of the online risks that can occur, especially in online learning.